FACTORS RELATED TO ECTOPIC PREGNANCY IN RSUD R.A KARTINI JEPARA - Muhammad Fikri Hanif Raza Pradana; Yuli Trisetiyono; Bambang Hariyana; Muhammad Besari Adi Pramono (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Ectopic Pregnancy (EP) is a pregnancy outside the womb that ends with a rupture. Bleeding is one of the causes of the increase in Maternal Mortality Rate (MMR) by 24.5% in Central Java Province in 2017. Research to determine the factors associated with the occurrence of EP needs to be known so that the incidence of EP and MMR in Indonesia can be controlled.Purpose: This study aimed to see the incidence of EP and analyzing the relationship between age and parity with the incidence of EP in RSUD R.A Kartini Jepara.Methods: This study used an analytic observational method with a case-control research design. Sampling was done by consecutive sampling method. A total of 83 samples met the inclusion criteria, which were divided into 51 pregnant women with EP and 32 pregnant women without EP. Data were analyzed using descriptive test and Chi-square test. The factors assessed were age and parity. Other variables contained in medical records are included in the form of descriptive data.Results: The incidence of EP in RSUD R.A Kartini Jepara was 0.4% in 2017, 0.5% in 2018, and 0.3%  in 2019. In EP patients, it was found that 54.9% of patients had an education level of junior high school, 58.8% of patients had a salpingectomy procedure, 92.1% of patients whose EP location was in the tube and 60.7% of patients needed inpatient services for >4 days. The results of the bivariate analysis using the Chi-square test showed a significant relationship between parity (p = 0.029) and the incidence of EP (p <0.05). Meanwhile, age (p = 0.897) did not show a significant relationship with the incidence of EP (p> 0.05).Conclusion: The incidence of EP in RSUD R.A Kartini Jepara in was 0.4% in 2017, 0.5% in 2018, and 0.3%  in 2019. There is a relationship between parity and the incidence of EP. Meanwhile, age is not related to the incidence of EP in RSUD R.A Kartini Jepara. Keywords: Ectopic Pregnancy, Age, Parity